Estimation of heterosis and performance of crossbred Swedish dairy cows - Jönsson, Rebecka (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2015)
The heterosis effect and breed group effect of crossbreds between Swedish Holstein (SH) and Swedish Red (SRB) was estimated in this study. Observations on cows born between 1990 and 2012 were used to estimate the heterosis effect and breed group effect for several traits included in the Nordic breeding goals: production, fertility, udder health, calving performance, survival and other diseases. Breeding within the Holstein dairy breed has earlier been focused on increased milk production and conformation. This, combined with an intensive use of individual animals, has resulted in a radical increase of milk yield in the Holstein dairy cow population all over the world. However, this breeding strategy has resulted in increased inbreeding and several functional traits have impaired. SH and SRB are the most common dairy breeds used in Sweden. The Nordic countries has for a long time included several functional traits in the breeding goals for both SH and SRB. SRB has been able to keep a high production level and still maintain a high performance of functional traits, such as fertility. However, SH has suffered similar problems as the Holstein breed abroad since the breeding has been influenced by international standards. Crossbreeding between SH and SRB has been used in order to increase the performance of functional traits and break the negative consequences of inbreeding at herd level. Several crossbreeding studies abroad have shown promising results but there is little knowledge about the effect of crossbreeding in Sweden. The study showed that the crossbreds had a favourable heterosis effect in all lactations for all traits except for some health traits. The relative heterosis effect (RHE) for production traits in first lactation was favourable and significant (P < 0.05) and ranged from 1.9 % to 2.4 % for crossbreds with SRB as the paternal breed and SH as the maternal breed (SRB x SH), and from 3.4 % to 4.5 % for crossbreds with SH as the paternal breed and SRB as the maternal breed (SH x SRB). The RHE for the functional traits; fertility, calving performance and survival was favourable and significant (P < 0.05) in first lactation and ranged from 1.4 % to 13.0 % for SRB x SH and from 0.8 % to 12.3 % for SH x SRB. The greatest RHE was found for survival to 3rd lactation for both F1-crossbreds (13.0 % for SRB x SH and 12.3 % for SH x SRB). The smallest RHE was found for calving interval for both F1-crossbreds (1.4 % for SRB x SH and 0.8 % for SH x SRB). The RHE for udder health and other diseases ranged from 2.0 % to 26.8 % but few traits were significant. The breed group effect of crossbreds was higher than for purebred SH for fertility in all lactations and for calving performance in first and second lactation. Crossbreds also had a better survival rate and produced the same amount, or more, fat in 305-d lactation than purebred SH. The results suggest that crossbreeding is a good method to improve functional traits at herd level while still having the potential to produce the same amount of milk fat. The crossbreds also have the potential to maintain, or even increase, the profitability in the dairy production since crossbreds have a high production, high fertility, small proportions of calving difficulties and stillbirths, and the survival is greater than for their purebred contemporaries.